Namibia : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2009)
The Southern African Customs Union (SACU), the oldest customs union in the world, comprises Botswana, Lesotho, Namibia, Swaziland (known as the BLNS countries), and South Africa. This Selected Issues paper analyzes how policy has responded to the positive SACU revenue shock. It discusses the background and structure of SACU, and examines the fiscal responses of the BLNS countries to the SACU revenue surge. The paper also discusses useful international experience and a framework for fiscal response in these countries.